Comparative study of impact of animal source on physical, structural, and biological properties of bone xenograft. (12th July 2020) - Gashtasbi, Fatemeh; Hasannia, Shahriar; Hasannia, Sadegh; Mahdi Dehghan, Mohammad; Sarkarat, Farzin; Shali, Abbas
Abstract: Background: Due to the unique features of xenografts including large supply from donors, minimal risk of human disease transmission, and the lower cost of preparation and production compared to autografts and allografts, they are considered as attractive alternatives to traditional bone grafts. The animal source accessibility and production process have a direct correlation with the cost and quality of the final product. To evaluate whether the animal source of the bone has any effect on the physicochemical and histological properties of the final xenograft, three deproteinized bone grafts were prepared from sources that are easily available in Iran, including the bovine (DBB), camel (DCB), and ostrich (DOB). Methods: In the current study, three bone substitute materials intended to serve as bone xenografts were derived from the cow, camel, and ostrich using the thermochemical processing procedure. The physicochemical properties, in vitro cytocompatibility and in vivo bone regeneration capability of the prepared deproteinized bone grafts, were assessed and compared with OCS‐B as an approved product in the global market. Results: The physical tests confirmed the hydroxyapatite nature of the final products. SEM and BET analysis showed morphological and structural differences between the products due to differences in the animal sources. In vitro studies showed the prepared deproteinized bone was free of processing chemicals and was biocompatible with mouse fibroblast and myoblast cell lines. In vivo studies revealed that the bone formation capability of the DBB, DCB, and DOB has no significant difference with one another and with OCS‐B despite their structural differences. The DCB showed the highest graft residue after two month. No signs of immunogenicity were observed in the study groups compared to the blank group. Conclusion: DBB, DCB, and DOB may offer a favorable cell response and bone regeneration similar to those of commercial bovine bone material.